Water Blooms—A Potential Threat to Male Reproduction: Clues From Aquatics and Rodents - Liu, Shengdi; He, Bin; Li, Hua (Frontiers in Endocrinology, 2022)
Abstract Toxic cyanobacteria blooms are a potential threat to global aquatic ecosystems and human health. Microcystin-leucine-arginine (MC-LR) is the most toxic variant of microcystins (MCs), and exposure to MCs can damage the male reproductive system. Two electronic databases were searched for controlled studies of rodents and fishes published before September 2020. Effect sizes were calculated for eight main reproductive parameters, including sperm count, sperm motility, sperm morphology, serum testosterone, testis weight, serum follicle stimulating hormone (FSH), serum luteinising hormone (LH) and serum estradiol. Nine meta-analyses of individual parameters were conducted using R version 4.0.2. Fifteen studies were included in the meta-analysis. In the studies of rodents, exposure to MC-LR by intraperitoneal injection or intragastric administration yielded statistically significant effects on sperm count (standardised mean difference (SMD) = -1.7426 (95% CI: -2.2098 to -1.2754)), abnormal sperm rate (SMD = 1.6714 (95% CI: 0.9702 to 2.3726)), sper5% CI: -3.9811 to -1.7834)), testis weight (SMD = -2.8822 (95% CI: -3.9811 to -1.7834)) and serum FSH (SMD = 0.4707 (95% CI: 0.0659 to 0.8756) changes in serum testosterone (SMD = 0.5521 (95% CI: 0.1652; 0.9391)) and estradiol (SMD = 0.6398 (95% CI: 0.1896 to 1.0900)) concentrations are considered to be statistically significant. Dose–response analysis reflected the dynamic changes of male reproductive function caused by MC. Short-term exposure to MC-LR can affect the function of the male reproductive system in rodents and fish. Elevated dosage or extended exposure time may worsen the damage. Human-related research on MC-LR exposure is very necessary to protect health and the water environment.